To Know or Not to Know? Theta and Delta Reflect Complementary Information about an Advanced Cue before Feedback in Decision-Making - Wang, Jing; Chen, Zhaofeng; Peng, Xiaozhe; Yang, Tiantian; Li, Peng; Cong, Fengyu; Li, Hong (Frontiers in Psychology, 2016)
To investigate brain activity during the reinforcement learning process in social contexts is a topic of increasing research interest. Previous studies have mainly focused on using electroencephalograms (EEG) for feedback evaluation in reinforcement learning tasks by measuring event related potentials (ERPs). Few studies have investigated the time-frequency (TF) profiles of a cue that manifested whether a following feedback is available or not after decision-making. Moreover, it remains unclear whether the TF profiles of the cue interacts with different agents to whom the feedback related. In this study we used the TF approach to test EEG oscillations of the cue stimuli in three agents (‘Self’, ‘Other’, and ‘Computer’) conditions separately. The results showed that the increased central-posterior delta power was elicited by the feedback unavailable cues more so than with the feedback available cue within 200-350 ms after the onset of the cue, but only in the self-condition. Moreover, a frontal-central theta oscillation had enhanced power when following the feedback unavailable cue as opposed to the feedback available cue across three agencies. These findings demonstrated that the cue for knowing an outcome produced reward prediction error (RPE)-like signals, which were mirrored by the delta and theta oscillations during decision-making. More importantly, the present study demonstrated that the theta and delta oscillations reflected separable components of the advanced cue processing before the feedback in decision-making.